A field vaccine trial in Tanzania demonstrates partial protection against malignant catarrhal fever in cattle. Issue 6 (3rd February 2016) - Lankester, F.; Russell, G.C.; Lugelo, A.; Ndabigaye, A.; Mnyambwa, N.; Keyyu, J.; Kazwala, R.; Grant, D.; Percival, A.; Deane, D.; Haig, D.M.; Cleaveland, S.
Highlights: We carried out the first field trial of a vaccine against malignant catarrhal fever. The vaccine was shown to be safe for use in Tanzanian cattle. The vaccine provided a 56% reduction in transmission of virus to cattle. Non-fatal MCF infections in cattle were more common than previously reported. Abstract: Malignant catarrhal fever (MCF) is a fatal lymphoproliferative disease of cattle that, in East Africa, results from transmission of the causative virus, alcelaphine herpesvirus 1 (AlHV-1), from wildebeest. A vaccine field trial involving an attenuated AlHV-1 virus vaccine was performed over two wildebeest calving seasons on the Simanjiro Plain of northern Tanzania. Each of the two phases of the field trial consisted of groups of 50 vaccinated and unvaccinated cattle, which were subsequently exposed to AlHV-1 challenge by herding toward wildebeest. Vaccination resulted in the induction of virus-specific and virus-neutralizing antibodies. Some cattle in the unvaccinated groups also developed virus-specific antibody responses but only after the start of the challenge phase of the trial. PCR of DNA from blood samples detected AlHV-1 infection in both groups of cattle but the frequency of infection was significantly lower in the vaccinated groups. Some infected animals showed clinical signs suggestive of MCF but few animals went on to develop fatal MCF, with similar numbers in vaccinated and unvaccinated groups. This study demonstrated a baseline level of MCF-seropositivity among cattle in northern Tanzania of 1% and showed that AlHV-1 virus-neutralizing antibodies could be induced in Tanzanian zebu shorthorn cross cattle by our attenuated vaccine, a correlate of protection in previous experimental trials. The vaccine reduced infection rates by 56% in cattle exposed to wildebeest but protection from fatal MCF could not be determined due to the low number of fatal cases.